USE OF SPECIAL KNOWLEDGE IN THE INVESTIGATION OF CRIMINAL OFFENCES AGAINST PEACE AND SECURITY OF MANKIND (Lex localis - Journal of Local Self-Government, 2025)
The article highlights the role of specialized knowledge in the investigation of criminal offenses against the peace and security of mankind in conditions of large-scale aggression, emphasizing the interdisciplinary nature of examinations and the need for their harmonization with international standards of evidence. The focus is on the combination of forensic, DNA, explosives, ballistic, environmental, linguistic, psychological and digital examinations as a basis for forming a holistic evidentiary picture. The importance of modern technologies, in particular satellite analytics, 3D modeling, big data and mobile DNA laboratories, for the operational documentation of crimes and increasing the reliability of evidence is substantiated. Legal and organizational barriers associated with the recognition of the conclusions of foreign experts, ensuring the chain of custody of evidence and access to crime scenes are highlighted. Areas of improvement are proposed: accreditation of international experts, unification of methodologies, development of interdisciplinary educational programs and standardization of work with digital evidence. The prospects for the integration of artificial intelligence and cyber expertise are shown under the condition of ethical and procedural guarantees. The results have practical significance for increasing the efficiency of national investigations and the admissibility of evidence in international proceedings.